Do ensino da língua à língua no ensino - Figueiredo, Olívia Maria Ferreira Gonçalves (Linguarum Arena, 2018)
In this article we offer an overview of the main trends that have been the methodological basis of the field of mother tongue didactics, particular by over the last fifty years, relating essential aspects such as: psychological, linguistic and pedagogical. Methods based on essential traits of communicative methodology are analysed. The need to establish principles aimed at pointing out each learning situation are highlighted.